Narcas: the secret rise of women in Latin America's cartels - Bonello, Deborah (Beacon Press, 2023)
"Drug transporters. Money launderers. Killers. Street drug vendors. Weapons traffickers. Kidnappers. Extortionists. VICE journalist Deborah Bonello reports from the trenches in this first-ever in-depth exploration of the hidden power women wield in Latin American drug cartels"--